Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1471-2407-9-38
|View full text |Cite
|
Sign up to set email alerts
|

Activity of mevalonate pathway inhibitors against breast and ovarian cancers in the ATP-based tumour chemosensitivity assay

Abstract: Previous data suggest that lipophilic statins such as fluvastatin and N-bisphosphonates such as zoledronic acid, both inhibitors of the mevalonate metabolic pathway, have anti-cancer effects in vitro and in patients. We have examined the effect of fluvastatin alone and in combination with zoledronic acid in the ATP-based tumour chemosensitivity assay (ATP-TCA) for effects on breast and ovarian cancer tumour-derived cells. Both zoledronic acid and fluvastatin showed activity in the ATP-TCA against breast and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…40) Moreover, it was reported that a combination of ZOL and FLU had a high safety margin and possessed no potential for drug interactions when used with other cancer cell lines. 30,41,42) There are controversies over the inhibition mechanism of the mevalonate pathway by NBPs and statins. The molecular mechanism of NBPs is usually due to the inhibition of FPP synthase and loss of signaling in the downstream pathway of small GTPases, such as Ras proteins.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…40) Moreover, it was reported that a combination of ZOL and FLU had a high safety margin and possessed no potential for drug interactions when used with other cancer cell lines. 30,41,42) There are controversies over the inhibition mechanism of the mevalonate pathway by NBPs and statins. The molecular mechanism of NBPs is usually due to the inhibition of FPP synthase and loss of signaling in the downstream pathway of small GTPases, such as Ras proteins.…”
Section: )mentioning
confidence: 99%
“…26,27) Several studies have focused on the cytotoxic effects of fluvastatin (FLU), which inhibits cell proliferation, suppresses angiogenesis, and triggers apoptosis. 28,29) Although the antitumor effect of the combination of ZOL and FLU has been investigated in other types of cancer, 30,31) it was not reported whether this combination treatment has a synergistic cytotoxic effect on pancreatic cancer cells or not. We evaluated the synergistic antiproliferative effect on two types of pancreatic cancer cell lines in vitro.…”
mentioning
confidence: 99%
“…ATP tumour chemosensitivity assays have been recommended to assess the viability of chemotherapy for the treatment of primary recurrent platinum-resistant epithelial ovarian cancer [421][422][423][424][425][426]. A combination of zoledronic acid and fluvastatin has been claimed to have activity against ovarian (and breast) cancer based on this assay [427]. A 2 receptor antagonism inhibits angiogenic activity of human ovarian cancer cells [428].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…The assay is particularly helpful for the in vitro design of new combinations, particularly where there was a molecular hypothesis to test. For instance, we were able to show that the effect of mevalonate pathway inhibitors was limited, but that they enhanced the effect of N-bisphosphonates, probably via the production of metabolites not normally present in the cell (11). We have most recently used the assay to show that EGFR and PI3K blockade is synergistic in ovarian cancer cells (Glaysher et al, unpublished data).…”
Section: The Atp-tcamentioning
confidence: 92%